Early childhood growth and nutritional status in India: trends in five National Family Health Surveys spanning 1992 and 2021 - Kundu, Ramendra Nath; Liczbińska, Grażyna; Gautam, Rajesh K.; Bharati, Susmita; Pal, Manoranjan; Bharati, Premananda; Malina, Robert M. (European journal of clinical nutrition, 2025)
Background/Objective To evaluate the weight and height status of under-five children between 1992 and 2021 in relation to nutritional context. Subjects/Methods The study is based on the lengths/heights and weights of children <5 years in five national surveys ( n = 505,026). After evaluating normality of the distributions, heights, and weights were expressed as z -scores relative to the WHO reference. Nonparametric tests were used as the heights and weights did not have normal distributions. Results Heights and weights of boys and girls increased systematically, on average, across the five national surveys, indicating improvement in nutritional status over time. Nevertheless, median z -scores for height and weight relative to the WHO reference indicated the persistence of relatively poor nutritional status across the surveys. Conclusions The growth status of Indian children <5 years improved over three decades, indicating that national initiatives promoting child health had a positive impact. Unfortunately, the nutritional status of significant numbers of children has not sufficiently improved and merits further attention.